coaching AS AN APPROACH TO MOTIVATION IN ADOLESCENT ATHLETES (Fiep Bulletin - online, 2014)
This work deals with theoretical foundations of motivation and analyzes the different motivational theories and principles applied in sports. A coaching approach was focused in terms of increase on motivation of teenaged sportspersons. In the research project a coaching approach was examined and compared with a traditional conduct and the GRO W method has been used as a motivational instrument. The results obtained by means of  sychodiagnostic inventory and motivational  uestionnaire, constructed and examined by students for this purpose, showed the positive influence of coaching and the GRO W method on a motivational level of the experimental group compared to control one. Coaches who have been systematically trained in coaching and in the GRO W method as well considered these tools as an efficient way to improve internal motivation for teenagers in the field of sport performance.
Keywords: extrinsic and intrinsic motivation; transformational leading; coaching; GRO W method